The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1677/joe-07-0392
|View full text |Cite
|
Sign up to set email alerts
|

A sexually dimorphic distribution pattern of the novel estrogen receptor G-protein-coupled receptor 30 in some brain areas of the hamster

Abstract: The isolation of the G-protein-coupled receptor 30 (GPR30), an orphan membrane receptor unrelated to nuclear estrogen receptors (ERs), has become a key factor towards the unraveling of rapid estrogen action. This membrane receptor together with cellular signaling intermediaries, i.e., extracellular signaldependent kinases 1 and 2, may promote neuronal proliferation and differentiation activities. In the present study, an evident gene expression pattern of GPR30 characterized postnatal 7 (young) and 60 (adult) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 26 publications
0
23
1
Order By: Relevance
“…Moreover, a high level of GPER immunoreactivity was observed in the striatum and thalamus in both sexes. These findings are, however, in contrast to those of Canonaco et al [22] who reported that a sexually dimorphic GPER expression pattern occurs in the hypothalamus and thalamus of the hamster. Nevertheless, there is accumulating evidence that GPER distribution in the brain is typically quite similar between males and females.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, a high level of GPER immunoreactivity was observed in the striatum and thalamus in both sexes. These findings are, however, in contrast to those of Canonaco et al [22] who reported that a sexually dimorphic GPER expression pattern occurs in the hypothalamus and thalamus of the hamster. Nevertheless, there is accumulating evidence that GPER distribution in the brain is typically quite similar between males and females.…”
Section: Discussioncontrasting
confidence: 99%
“…3A). In addition, G-1-induced relaxation was unaffected by pretreating arteries with 10 M 1 H- [1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one, a selective inhibitor of guanylyl cyclase activity (n ϭ 5; data not shown). However, similar to 17␤-estradiol, the relaxation effect of G-1 was dependent upon potassium efflux from CASM cells.…”
Section: Resultsmentioning
confidence: 95%
“…Several studies have implicated hypothalamic Erk 1/2 in the regulation of energy homeostasis [46,47] and activation of the Erk 1/2 signaling pathway in the CNS mediates the anorectic effects of leptin [48] and CCK [23]. Canonaco et al, reported overlapping distribution of Erk 1/2 with GPER in most brain areas [49] of the hamster. Here, we demonstrate for the first time that female OVX GPER KO mice have reduced 17β-estradiol-induced pErk 1/2 when compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%